Wear Particles, Periprosthetic Osteolysis and the Immune System - Goodman, Stuart B. (2007)
The immune system modulates many key biological processes in humans. However, the exact role of the immune system in particle-associated periprosthetic osteolysis is controversial. Human tissue retrieval studies, in vivo and in vitro experiments suggest that the immune response to polymer particles is nonspecific and macrophage mediated. Lymphocytes may modulate this response however direct lymphocyte activation by polymer particle-protein complexes seems unlikely. However, metallic byproducts may complex with serum proteins and lead to a Type IV, lymphocyte mediated immune reaction. In predisposed individuals, this reaction may rarely lead to persistent painful joint effusions, necessitating debridement and excision of the bearing surfaces of the prosthesis. In these patients, retrieved periprosthetic tissues exhibit histological evidence of perivascular lymphocytic cuffing. These findings are worrisome, given the fact that increasing numbers of metal-on-metal joint implants are being implanted in younger more active individuals worldwide.